CCVD synthesis of carbon-encapsulated cobalt nanoparticles for biomedical applications - Lukanov, Petar; Anuganti, Vijay K.; Krupskaya, Yulia; Galibert, Anne-Marie; Soula, Brigitte; Tilmaciu, Carmen; Velders, Aldrik H.; Klingeler, Rüdiger; Büchner, Bernd; Flahaut, Emmanuel (Advanced functional materials, 2011)
Carbon-encapsulated ferromagnetic Cobalt nanoparticles (CoC) have been synthesized by catalytic chemical vapour deposition (CCVD). The nanoparticles, mainly ranging between 10 and 15 nm, are tightly encapsulated by 2-3 concentric graphitic carbon shells and protected from oxidation. Because of their magnetic properties (saturation magnetization of 106 emu/g and a coercivity HC of 250 Oe), Co@C nanoparticles have been investigated for hyperthermia application. Although the observed values of the specific absorption rate (28.7 W/gCo@C at 30 kA/m and 215.4 W/gCo@C at 70 kA/m) are slightly lower than required in actual hyperthermia therapies, the observed strong heating effect provides a very promising starting point for future clinical application. It is also demonstrated that these nanoparticles can at the same time be used for magnetic resonance imaging (MRI) with an efficiency comparable to commercially available T2 contrast agents.